Highly dispersed Ni-Mo encapsulated in hollow mesoporous ZSM-5 as an efficient catalyst for tetralin conversion to light aromatics - Mengdi Wang; Limin Zhang; Haoqing Zhang; Jiaming Wu; Keyan Li; Xinwen Guo (Fuel, 2026)

Synergistic effects of spray pre-cooling and prochloraz treatment on postharvest quality maintenance of 'Guiwei' litchi - Jiaming Guo; Jianye Wang; Dinghe Wu; Peng Guo; Zhiwu Ding; Jingrui Meng; Haoran Dai; Jiahang Qiao; Zilong Deng; Enli Lü (Postharvest Biology and Technology, 2026)

Potential of individual-scale phenological measurements for improving wood productivity and maintaining genetic diversity in forest management - Haruka Sano; Tai-Shen Chen; Jiaming Yan; Naoko Miura; Minoru Inamori; Wei Guo; Sachiko Isobe; Kazutaka Kusunoki; Hiroyoshi Iwata (Forest Ecology and Management, 2026)

Experimental study of condensation induced water hammer caused by the accumulation of condensate water in the steam pipeline - Minchao Liang; Jiaming Zhao; Jiarui Zhang; Rongyang Xue; Yili Yang; Wentao Guo; Shengfei Wang (Annals of Nuclear Energy, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

A bibliometric analysis of global duckweed research (2015–2025): research trends, international collaborations, and emerging themes - Jiaming Wang; Zhenghong Peng; Zuoyue Duan; Yaojun Zhou; Hongling Zhu; Shijun You; Zhiyi Peng; Mengni Shi; Qulian Guo; Wenjun Liu; Ling Guo (Hydrobiologia, 2026)

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

How built environments shape leisure jogging styles: Nonlinear and interactive effects across objective and subjective dimensions - Wei Yang; Mengjia Yin; Longyang Huang; Jiaming Sun; Caixuan Guo; Xin Fan; Jingjing Li (Journal of Transport Geography, 2026)

Corrigendum to “Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data” [Int. J. Coal Geol. 320 (2026) 104999] - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Microbial nutrient stimulation enhances in situ methanogenesis ~ 900 m depth in coalbeds: evidence from long-term field trial in Hancheng Block - Weidong Yan; Jiaming Yang; Zhidong Guo; Yingming Wang; Hui Wang; Wenhui Meng; Yang Yuan; Hailin Yang; Shoushuai Feng (Systems Microbiology and Biomanufacturing, 2026)

Unveiling the Hidden Resistome: A Comprehensive Risk Assessment of Latent Antibiotic Resistance Genes in China's Wastewater - Wenshan Yang; Jiaming Guo (Environmental Microbiology, 2026)
Wastewater systems are important reservoirs of antibiotic resistance genes (ARGs), but the ecological and health risks of numerous latent ARGs (LARGs) remain unclear. In this study, we analysed 636 wastewater metagenomic samples from China and constructed a database containing 1587 LARGs. Across all environments, LARGs encoding serine‐β‐lactamases were the most abundant and prevalent. A comprehensive risk assessment, integrating host pathogenicity, gene mobility and environmental prevalence, was performed on 561 LARGs identified in metagenome‐assembled genomes. Most LARGs exhibited low levels across all three dimensions, suggesting limited transmission risk. Nevertheless, 37 high‐risk LARGs were identified, indicating non‐negligible threats. Functional validation showed that the top three extremely high‐risk LARGs significantly enhanced host resistance to ampicillin and ciprofloxacin when expressed in Escherichia coli , while AlphaFold3 revealed typical resistance protein folding, further supporting their functional activity. Horizontal gene transfer analysis indicated that these high‐risk genes have disseminated from wastewater to natural water bodies such as rivers via plasmid‐mediated mechanisms. Collectively, wastewater acts not only as an ‘accumulation pool’ for LARGs but also as a potential source releasing ‘super‐risky’ resistance gene into the environment. Therefore, urgent efforts are needed to monitor and control these high‐risk LARGs and their mobile genetic elements to block their environmental spread.

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Anthropogenic sustained increase in near bottom suspended particulate matter concentration of the deep marginal sea - Zhuangcai Tian; Xiujun Guo; Jiaming Xiang; Tong Li; Jinran Wu (Environmental Research, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Synergistic layer engineering for high-efficiency blue emission in pure-bromide quasi-2D perovskite light-emitting diodes - Jiaming Yu; Bochao Jia; Shuguang Zhang; Yachun Guo; Yue Liang; Jiangshan Chen; Linfeng Lan; Junbiao Peng (Chemical Engineering Journal, 2026)

Targeting S100A4+ macrophages to reverse radiation-induced Leydig cell fibrosis with a therapeutic nanosystem - Yewei Bao; Heng Gong; Weihao Sun; Lei Wang; Tianqi Wang; Boyang Zhang; Guanyu Ren; Shuguang Piao; Cheng Zheng; Jiaming Guo; Linhui Wang; Xinxin Gan (Chemical Engineering Journal, 2026)

Monitoring contaminant removal during in situ chemical oxidation using cross-borehole resistivity tomography and hydrogeology - Teng Xia; Jiaming Zhang; Ruijue Zhao; Miao Li; Shupeng Li; Lili Guo; Deqiang Mao (Journal of Hydrology, 2026)

Targeting argH to attenuate Aeromonas dhakensis virulence: A metabolic checkpoint for biofilm formation and stress adaptation - Xueqian Wang; Chenlu Yang; Xuesong Li; Wei Feng; Jianguo Zhao; Yukun Wu; Shuai Ye; Meng Zhao; Hanzeng Li; Jiaming Ju; Guiying Guo; Lixia Fan; et al. (Veterinary Microbiology, 2025)

Spatial-interaction-context and temporal-attention U-Net model for spatio-temporal prediction of Sea Surface Temperature field - Jiaming Ma; Jun Song; Junru Guo; Yanzhao Fu; Yu Cai; Yuan Zhang; Jie Tian; Ming Li (Regional Studies in Marine Science, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

Enhancing phyto-microbial remediation of petroleum-contaminated soil using sophorolipid-modified biochar: Metagenomic and metabolomic insights - Yuhang Chen; Fumei Wang; Jiaqi Gao; Qinglong Liu; Jiaming Guo; Huan Liu (Environmental Research, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Digital simulation of condensation and water loss in ventilated lychee packaging - Jicheng Lin; Xiaodan Zhang; Yihong Jiang; Dongfeng Liu; Wei Cai; Guopeng Lin; Zhiwu Ding; Enli Lü; Jiaming Guo (Biosystems Engineering, 2025)

Insight shift from laboratory to industrialization for tail gas-based ethanol production - Jiaming Gu; Danfeng Wang; Qun Shen; Li Shang; Guofei Shen; Nannan Sun; Shuhuan Tong; Wei Chao; Yangyang Guo; Wei Wei (Chemical Engineering Journal, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Towards efficient in situ gas thermal desorption remediation assisted with cross-borehole resistivity tomography - Teng Xia; Jiaming Zhang; Miao Li; Shupeng Li; Lili Guo; Peng Liu; Dixiang Wang; Deqiang Mao (Water Research, 2025)

Co-incorporation of lattice S and P into nano zero-valent iron induces multiple Kirkendall effects for enhanced trichloroethylene reduction efficiently - Yinghao Shi; Honghong Lyu; Saisai Guo; Jiaming Guo; Feilong Gao; Jingchun Tang (Journal of Hazardous Materials, 2025)

Dynamic response of seabed in wind power of deep-shallow sea induced by internal solitary waves - Jiaming Xiang; Zhuangcai Tian; Youkou Dong; Enjin Zhao; Lei Song; Jianhua Yue; Guoqing Zhou; Xiaolei Liu; Xiujun Guo; Yonggang Jia (Marine Georesources & Geotechnology, 2025)

FeS/rGO modified cathode for enhanced electrochemical activity and TCE degradation in PS-MFC system - Chunji Li; Guanlin Chen; Jiaming Guo; Yinghao Shi; Jikun Li; Jingchun Tang (Journal of Environmental Chemical Engineering, 2025)

Catalytic ozonation of sulfamethoxazole using loaded CuOx/MgO-SiO2 silica aerogel catalyst: Performance, mechanisms and toxicity - Lanhe Zhang; Jiaming Wu; Jian Zhang; Jingbo Guo (Environmental Research, 2025)

One-dimensional LATP nanofiber reinforced PEO solid composite electrolyte for all-solid-state lithium-ion batteries with excellent cycling performance - Yudi Guo; Erqing Zhao; Weifang Su; Zhe Liu; Jiaming Li (Chemical Engineering Journal, 2025)

Engineering cuttlefish melanin nanoparticles: A dual-action therapy for acute radiation syndrome and combined radiation-wound injuries via regulating Bcl-2 family proteins and caspases in the apoptotic process - Zhemeng Zhao; Bin Hu; Danfeng Zhang; Xinyue Cui; Wen Ding; Tongshuai Wang; Jingyi Wang; Ziyi Guo; Yingtang Zhou; Shige Wang; Jiaming Guo (Chemical Engineering Journal, 2025)

Genome-wide identification of the SmPHR gene family in Salvia miltiorrhiza and SmPHR7-mediated response to phosphate starvation in Arabidopsis thaliana - Xinxin Wang; Renjun Qu; Shiwei Wang; Jiaming Peng; Juan Guo; Guanghong Cui; Tong Chen; Meilan Chen; Ye Shen (Plant Cell Reports, 2025)

A functional fluorine (F)-containing oxidiser of nano-networked NH4CuF3 to improve the combustion efficiency of Al powder - Xiandie Zhang; Haozhe Li; Xuxu Cui; Weiduo Fei; Xinwen Ma; Jiaming Liu; Pingyun Li; Xiaode Guo; Xiang Zhou (Fuel, 2025)

A black tea quality testing method for scale production using CV and NIRS with TCN for spectral feature extraction - Jianhua Liang; Jiaming Guo; Hongling Xia; Chengying Ma; Xiaoyan Qiao (Food Chemistry, 2025)

Tracking Cr(VI) removal with spectral induced polarization under ZVI and AC synergetic remediation - Xinmin Ma; Jiaming Zhang; Chen Chao; Shiliang Liu; Khalil Ur Rahman; Shupeng Li; Lili Guo; Deqiang Mao (Environmental Research, 2025)

Efficient Removal of Cr(VI) by Bamboo-Derived Biochar Supported Nano Zero-Valent Iron: Insights into Performance and Mechanism - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Yunlong Zhu; Jianbing Lu; Yang Gao; Mingjuan Zhang; Wenjing Xue (Water, Air, & Soil Pollution, 2025)

Achieving remarkable charge transfer through the depolarization field in the 2D/2D S-scheme heterojunction consisted of C3N5 nanosheets and layered ferroelectric Bi3TiNbO9 for photocatalytic hydrogen production - Haotian Guo; Jinhui Jiang; Jiaming Liang; Chunyang Wen; Xinguo Xi; Pengyu Dong (Chemical Engineering Journal, 2025)

Construction of La1−xSrxNiO3/g-C3N4 type-Z heterojunctions with enhanced visible-light photocatalytic degradation of organic pollutants - Pengke Yu; Jiaxing Guo; Liang Guo; Yaqin Deng; Juntao Tan; Qunang Xu; Qingmao Zhang; Jiaming Li (Environmental Research, 2024)

The dynamics of some exact solutions to a ( 3 + 1 ) -dimensional sine-Gordon equation - Jiaming Guo; Maohua Li (Wave Motion, 2024)

Evaluation of a novel attapulgite loaded sulfidized nanoscale zero-valent iron for immobilization of Pb in sediment: Performance, microenvironmental response, and mechanisms - Siqi Wen; Weilong Lin; Qi He; Yiqun Xu; Xiaoyu Shi; Jiaming Guo; Yang Gao; Wenjing Xue (Chemical Engineering Journal, 2024)

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

Enhanced reductive degradation of trichloroethylene by ball milled nitridation of bimetallic Ni-ZVI: Combination effect of electron transfer and catalytic hydrogenation - Yinghao Shi; Dong Wang; Jiaming Guo; Feilong Gao; Linan Liu; Jingchun Tang (Journal of Cleaner Production, 2024)

Preparation of salicylic acid nano-protectant with dual synergistic mechanism: High direct fungicidal activity and plant defence toward cotton Verticillium wilt - Jiaming Yin; Jiajia Zhao; Zeng Wang; Fan Xue; Qi Wang; Huiming Guo; Hongmei Cheng; Jie Li; Jie Shen; Meizhen Yin; Xiaofeng Su; Shuo Yan (Chemical Engineering Journal, 2024)

Erratum to: Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Effects of DeSUMOylated Spastin on AMPA Receptor Surface Delivery and Synaptic Function Are Enhanced by Phosphorylating at Ser210 - Wenbin Zhang; Jiaqi Zhang; Zhongqi Zhang; Shuhan Cha; Jiong Li; Li Chen; Jiaming Wu; Jijun Teng; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

An Improved Inception Network to classify black tea appearance quality - Jiaming Guo; Jianhua Liang; Hongling Xia; Chengying Ma; Jicheng Lin; Xiaoyan Qiao (Journal of Food Engineering, 2024)

Affecting factors and mechanism of removing antibiotics and antibiotic resistance genes by nano zero-valent iron (nZVI) and modified nZVI: A critical review - Wenjing Xue; Xiaoyu Shi; Jiaming Guo; Siqi Wen; Weilong Lin; Qi He; Yang Gao; Rongzhong Wang; Yiqun Xu (Water Research, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Image-guided structure-constrained inversion of electrical resistivity data for improving contaminations characterization - Xinmin Ma; Jieyi Zhou; Jing Li; Jiaming Zhang; Chunmei Han; Lili Guo; Shupeng Li; Deqiang Mao (Computers & Geosciences, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Minor chromium passivation of S-ZVI enhanced the long-term dechlorination performance of trichlorethylene: Effects of corrosion and passivation on the reactivity and selectivity - Jiaming Guo; Dong Wang; Yinghao Shi; Honghong Lyu; Jingchun Tang (Water Research, 2024)

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

Sulfidation of zero-valent iron for enhanced reduction of chlorinated contaminants: A review on the reactivity, selectivity, and interference resistance - Jiaming Guo; Feilong Gao; Chengfang Zhang; Shakeel Ahmad; Jingchun Tang (Chemical Engineering Journal, 2023)

Insights into chloride sorption and phase transformation of the synthesized Ca-Al bimetallic oxides in flue gas desulfurization wastewater - Zhen Zhou; Qiaoling Zhu; Ziwei Lan; Yuyue Yang; Li Zeng; Chengrui Liu; Jiaming Guo; Xiaodan Zhao (Chemical Engineering Journal, 2023)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Statistical modeling and dependence analysis for tide level via multivariate extreme value distribution method - Ali Tian; Xufeng Shu; Jiaming Guo; Haoyun Li; Renchuan Ye; Peng Ren (Ocean Engineering, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Recent advances in sulfidized nanoscale zero-valent iron materials for environmental remediation and challenges - Wenjing Xue; Jun Li; Xinyu Chen; Hongdou Liu; Siqi Wen; Xiaoyu Shi; Jiaming Guo; Yang Gao; Jian Xu; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Tetrabromobisphenol A transformation by biochar supported post-sulfidated nanoscale zero-valent iron: Mechanistic insights from shell control and solvent kinetic isotope effects - Feilong Gao; Mingyi Zhang; Shakeel Ahmad; Jiaming Guo; Yinghao Shi; Xinzuo Yang; Jingchun Tang (Journal of Hazardous Materials, 2023)

Enhancement of sodium salty taste modulate by protease-hydrolyzed Gum Arabic - Kailin Ye; Jiaming Qi; Yang Zhang; Jinmei Wang; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2023)

The Intensification of Prolonged Cooling Climate-Exacerbated Late Ordovician–Early Silurian Mass Extinction: A Case Study from the Wufeng Formation–Longmaxi Formation in the Sichuan Basin - Zhibo Zhang; Yinghai Guo; Hengye Wei; Chunlin Zeng; Jiaming Zhang; Difei Zhao (Journal of Marine Science and Engineering, 2023)
The Late Ordovician–Early Silurian period was a significant transitional phase in geological history and has garnered global interest. This study focuses on the black shale series of the Wufeng Formation–Longmaxi Formation of the Upper Ordovician–Lower Silurian period in the Sichuan Basin. Based on the logging curves and lithological characteristics of the Yucan-1 Well, 46 black shale samples were collected from the target layer section for clay mineral XRD (46 samples) analysis and whole-rock XRF (14 samples) analysis. The results indicate that three third-order sequences (SQ1, SQ2, and SQ3) are present in the Wufeng Formation–Longmaxi Formation of the Yucan-1 Well, and two subfacies and three microfacies were identified. In conjunction with the characteristics as well as the characteristic parameters of whole-rock oxide and clay mineral content ((I/C), (S + I/S)/(I + C), CIA, CIA-error, CIW, PIA, MAP, and LST), the Wufeng Formation–Longmaxi Formation of the Yucan-1 Well is divided into three intervals. Interval I is the Wufeng Formation. During this interval, weathering intensity, surface temperature, and precipitation gradually decreased, while the climate shifted from warm and humid to cold and dry. This corresponds to two pulse-type biological extinction events and represents an interval of increasing organic carbon burial. Interval II encompasses the bottom-middle part of the Longmaxi Formation. Weathering intensity, surface temperature, and precipitation were characterized by smooth, low values. Subsequently, the climate was predominantly cold and dry. This was the primary interval of organic carbon enrichment. Interval III extends from the upper part to the top of the Longmaxi Formation. Weathering intensity, surface temperature, and precipitation gradually increased. The climate transitioned from cold and dry to warm and humid. Organic carbon burial gradually decreased, while sea levels dropped. This indicates that climate cooling was the primary controlling factor for this biological extinction event. In combination with previous divisions of graptolite zones in the Yucan-1 Well, it is postulated that this biological extinction event may primarily have been pulse extinction. The continuous cooling of the climate in the later period led to the continuous extinction of organisms that survived the disaster. Until approximately 438.76 Ma at the top of the Longmaxi Formation, the climate environment recovered to pre-extinction conditions, with a transition to a warm and humid climate again.

Observation of black carbon in Northern China in winter of 2018–2020 and its implications for black carbon mitigation - Yang Wang; Qiuge Ju; Zhenyu Xing; Jiaming Zhao; Song Guo; Fuxing Li; Ke Du (Science of The Total Environment, 2023)

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

Efficient separation and comprehensive extraction of aluminum, silicon, and iron from coal fly ash by a cascade extraction method - Xiaodan Zhao; Li Zeng; Jiaming Guo; Qiaoling Zhu; Zhuojun Huang; Lifeng Lin; Xuanang Chen; Jing Cao; Zhen Zhou (Journal of Cleaner Production, 2023)

Quality retention and delay postharvest senescence of figs (Ficus carica L.) using 1-methylcyclopropene and modified atmosphere packaging during cold storage - Cailian Wang; Jiaming Du; Dehua Hou; Xiaohong Guo; Qianting Liu; Linwen Liu; Yu Fang; Liping Kou (Food Bioscience, 2023)

In-depth understanding of catalytic and adsorbing effects in polysulfides conversion and rationally designing coaxial nanofibers for Li-S batteries - Jiaming Tian; Zihan Shen; Huiting Cheng; Xin Jin; Zhonghua Li; Yang Wen; Junfeng Hui; Shaohua Guo; Huigang Zhang; Qingshan Zhu (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Correction to: Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Comparative analysis of husk microstructure, fruit quality and concentrations of bioactive compounds of different pomegranate cultivars during low temperature storage - Qianting Liu; Xiaohong Guo; Jiaming Du; Yidan Guo; Xiaocheng Guo; Liping Kou (Food Bioscience, 2023)

Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Improving the detection accuracy of the nitrogen content of fresh tea leaves by combining FT-NIR with moisture removal method - Jiaming Guo; Han Huang; Xiaolong He; Jinwei Cai; Zhixiong Zeng; Chengying Ma; Enli Lü; Qunyu Shen; Yanhua Liu (Food Chemistry, 2023)

Optimization of a compact on-site stormwater runoff treatment system: Process performance and reactor design - Yangjie Qin; Chuanting Zhou; Siqi Yu; Hongjian Pang; Jiaming Guo; Jun Wei; Libing Wang; Yunxin Xing; Ying An; Zhen Zhou (Chemosphere, 2023)

Improved catalytic activity and stability of Cu/ZnO catalyst by boron oxide modification for low-temperature methanol synthesis - Fei Chen; Jiaming Liang; Fan Wang; Xiaoyu Guo; Weizhe Gao; Yasuharu Kugue; Yingluo He; Guohui Yang; Prasert Reubroycharoen; Tharapong Vitidsant; Noritatsu Tsubaki (Chemical Engineering Journal, 2023)

Effects of leaf scorch on chlorophyll fluorescence characteristics of walnut leaves - ChangJie Xing; ShiWei Wang; CuiFang Zhang; Tong Guo; HongLong Hao; ZhuoYa Zhang; Sheng Wang; JiaMing Shu (Journal of Plant Diseases and Protection, 2023)

In-situ construction of BiOBr/Bi2WO6 S-scheme heterojunction nanoflowers for highly efficient CO2 photoreduction: Regulation of morphology and surface oxygen vacancy - Jiaming Wu; Keyan Li; Siyu Yang; Chunshan Song; Xinwen Guo (Chemical Engineering Journal, 2023)

Phosphorylation of CRMP2 by Cdk5 Negatively Regulates the Surface Delivery and Synaptic Function of AMPA Receptors - Longfei Cheng; Keen Chen; Jiong Li; Jiaming Wu; Jiaqi Zhang; Li Chen; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2022)

Tilt deformation and instability of the slope for predicting rainfall-induced landslide - Handong Liu; Jing-jing Liu; Jiaxing Chen; Jiaming Luo; Wei Guo (Arabian Journal of Geosciences, 2022)

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

A Risk Assessment Method for Metro Shield Tunnel Construction Based on Interval Number - Yeqin Zhang; Jiaming Zhang; Hailin Guo; Yang Zhou; Guofu Ma; Cong Wang (Geotechnical and Geological Engineering, 2020)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

Effects of crude extracted proteins from supernatant of BCF-P and EGF on acid secretion - Yuqing Zhao; Tao Guo; Jiaming Qian (Molecular & Cellular Toxicology, 2015)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)

Extensive tRNA Gene Changes in Synthetic Brassica napus - Lijuan Wei; Zeshan An; Annaliese S. Mason; Meili Xiao; Ying Guo; Jiaming Yin; Jiana Li; Donghui Fu (Journal of Molecular Evolution, 2014)

Clinical Analysis of 15 Cases of Liver Nodular Regenerative Hyperplasia - Tao Guo; Jiaming Qian; Liming Zhu; Weixun Zhou; Feng Zhu; Gang Sun; Xiucai Fang (Cell Biochemistry and Biophysics, 2012)

Isolation and characterization of a novel EAR-motif-containing gene GmERF4 from soybean (Glycine max L.) - Gaiyun Zhang; Ming Chen; Xueping Chen; Zhaoshi Xu; Liancheng Li; Jiaming Guo; Youzhi Ma (Molecular Biology Reports, 2010)

Comparative analysis of distinct non-coding characteristics potentially contributing to the divergence of human tissue-specific genes - Qianli Huang; Jiaming Guo; Qq Ge; Jesse Li-Ling; Xueping Chen; Fei Ma (Genetica, 2009)

Evaporite karst and resultant geohazards in China - Lu Yaoru; Zhang Feng’e; Qi Jixiang; Xu Jiaming; Guo Xiuhong (Carbonates and Evaporites, 2002)